A strategy for dual-networked epoxy composite systems toward high cross-linking density and solid interfacial adhesion. (1st April 2023) - Seo, Heun Young; Im, Dohyun; Kwon, Young Je; Nam, Chae Yun; Kim, Se Hun; Nam, Taegu; Kim, Changki; Vivek, E.; Baek, Kyong-Youl; Cho, Kie Yong; Yoon, Ho Gyu
Abstract: Epoxy composites (ECs) are used as epoxy molding compound (EMC), which significantly protects the integrated circuits from the humid environment. One of the major limitations with ECs is their phenomena of moisture absorption in humid environments, which drastically reduces their mechanical properties and hinders them from gaining widespread industrial applications. The low cross-linking density of conventional epoxy composites that can lead to intrinsically providing hydrophilic sites and low activation energy in water molecule diffusion. Herein, a dual-networked epoxy composite system as a platform technique by adopting strategically designed poly (methyl methacrylate)- b -(dimethyl aminoethyl methacrylate) (PMD) as polymer compatibilizer to improve the water absorption resistance and mechanical properties derived from good interfacial adhesion and high cross-linking density of epoxy/silica composites were investigated. The as-prepared dual-networked epoxy composite system demonstrates a high-water absorption suppression of about 166.78% and a high tensile modulus of 4.6 GPa, compared to other epoxy composites. In addition, the current strategy has excellent expandability to various fillers also applicable to diverse epoxy composite systems. Highlights: The dual-networked system is newly developed for the epoxy composite system. Functionalized silica improves the cross-linking density in epoxy composites. The water absorption of ECFS composites was significantly suppressed. The acquired ECFS composites exhibit superior mechanical properties.